Respiratory mechanics and gas exchange in an ovine model of congenital heart disease with increased pulmonary blood flow and pressure - Soares, Joao Henrique N.; Raff, Gary W.; Fineman, Jeffrey R.; Datar, Sanjeev A. (Frontiers in Physiology, 2023)
In a model of congenital heart disease (CHD), we evaluated if chronically increased pulmonary blood flow and pressure were associated with altered respiratory mechanics and gas exchange. Respiratory mechanics and gas exchange were evaluated in 6 shunt, 7 SHAM, and 7 control age-matched lambs. Lambs were anesthetized and mechanically ventilated for 15 minutes with tidal volume of 10 mL/kg, positive end-expiratory pressure of 5 cmH2O, and inspired oxygen fraction of 0.21. Respiratory system, lung and chest wall compliances (Crs, CL and Ccw, respectively) and resistances (Rrs, RL and Rcw, respectively), and the profile of the elastic pressure-volume curve (%E2) were evaluated. Arterial blood gases and volumetric capnography variables were collected. Comparisons between groups were performed by one-way ANOVA followed by Tukey-Kramer test for normally distributed data and with Kruskal-Wallis test followed by Steel-Dwass test for non-normally distributed data. Average Crs and CL in shunt lambs were 30 and 58% lower than in control, and 56 and 68% lower than in SHAM lambs, respectively. Ccw was 52 and 47% higher and Rcw was 53 and 40% lower in shunt lambs compared to controls and SHAMs, respectively. No difference in %E2 was identified between groups. No difference in respiratory mechanics was observed between control and SHAM lambs. In shunt lambs, Rcw, Crs and CL were decreased and Ccw was increased when compared to control and SHAM lambs. Pulmonary gas exchange did not seem to be impaired in shunt lambs when compared to controls and SHAMs.